2021
DOI: 10.1101/2021.06.23.448673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering the Genetic Profiles Underlying the Intrinsic Organization of the Human Cerebellum

Abstract: Decoding the genetic profiles underlying the cerebellar functional organization is critical for uncovering the essential role of the human cerebellum in various high-order functions and malfunctions in neuropsychiatric disorders. However, no effort has been made to systemically address this. By combining transcriptome data with the intrinsic functional connectivity of the human cerebellum, we not only identified 443 network-specific genes but also discovered that their gene co-expression pattern correlated str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 122 publications
(250 reference statements)
0
2
0
Order By: Relevance
“…Differences in sample characteristics, for example, between the AHBA donors and the participants of our Chinese neuroimaging study, may furthermore require additional caution in interpreting imaging‐genetic findings. Finally, because the significant genes were not identified based on correlations with spatially defined phenotypes but obtained by PLS correlation analyses, the newly proposed strategy [90] that mitigates the bias of leveraging gene enrichment approach in the spatial transcriptomic data could not be directly used [91]. In addition, we used a multi‐gene‐list meta‐analysis to identify the shared and specific pathways between GGE‐related risk genes from GWAS and PLS1 significant genes, which could not be performed by the newly proposed strategy [90].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in sample characteristics, for example, between the AHBA donors and the participants of our Chinese neuroimaging study, may furthermore require additional caution in interpreting imaging‐genetic findings. Finally, because the significant genes were not identified based on correlations with spatially defined phenotypes but obtained by PLS correlation analyses, the newly proposed strategy [90] that mitigates the bias of leveraging gene enrichment approach in the spatial transcriptomic data could not be directly used [91]. In addition, we used a multi‐gene‐list meta‐analysis to identify the shared and specific pathways between GGE‐related risk genes from GWAS and PLS1 significant genes, which could not be performed by the newly proposed strategy [90].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible a GCE variation along the long axis of the hippocampus exists, gradual or parcellated, but is driven by a small number of genes or a specific subset of genes that is not captured in our analysis. A recent study examining the human cerebellum combined the Allen Human Brain Atlas (AHBA) transcriptome data with a cerebellar functional parcellation atlas and found that a majority of the 443 network specific genes were specific in the limbic (n = 170) and visual (n = 221) networks (Wang et al, 2021). Another recent study found that the location of human tissue samples extracted along the hippocampus long axis could be predicted within 2 mm using the expression pattern of less than 100 genes (Vogel et al, 2020), while our analysis included 4376 genes mapped in the AGEA dataset.…”
Section: Gene Co-expression Gradientsmentioning
confidence: 99%